Primary Mesenteric Undifferentiated Pleomorphic Sarcoma Masquerading as a Colon Carcinoma: A Case Report and Review of the Literature - Robert Diaz-Beveridge; Marcos Melian; Carlos Zac; Edwin Navarro; Dilara Akhoundova; Melitina Chrivella; Jorge Aparicio (Case Reports in Oncological Medicine)
Undifferentiated pleomorphic sarcoma (UPS) is the most common sarcoma that appears in older patients, usually in the extremities and the retroperitoneum. Other locations are rare. By definition, in UPS, although the malignant cells tend to appear fibroblastic or myofibroblastic, they should not show differentiation towards a more specific line of differentiation. In this sense, we report the case of an 80-year-old patient with an initial clinical diagnosis of a locally advanced colonic neoplasm that was later confirmed as a primary mesenteric UPS. Primary mesenteric UPS are extremely rare with less than 20 cases reported. We also review the pathologic and radiologic diagnostic criteria and the natural history of these tumours.